2021
DOI: 10.21203/rs.3.rs-143762/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of RYR2 Mutation with Tumor Mutation Burden, Prognosis and Antitumor Immunity in Patients with Esophageal Adenocarcinoma

Abstract: BackgroundEsophageal adenocarcinoma (EAC) remains a leading cause of cancer-related deaths worldwide, and demonstrates a predominant rising incidence in Western countries. Recently, immunotherapy has dramatically changed the landscape of treatment for many advanced cancers, the benefit in EAC thus far been limited to a small fraction of patients. MethodsUsing somatic mutations data of The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC), we delineated somatic mutation landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition to causing mutation-derived neoantigens, a high TMB can make tumors more immunogenic by inducing a T-cell-mediated immune response and releasing new antigens. [30][31][32][33] Therefore, we hypothesize that KMT2C and PEG3 mutations result in a higher TMB level in PAAD, activating the immune system to attack cancer. 34 During the progression of metastatic epithelial cancer, antigen mutations have recently been found in peripheral blood samples from patients with KMT2C mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to causing mutation-derived neoantigens, a high TMB can make tumors more immunogenic by inducing a T-cell-mediated immune response and releasing new antigens. [30][31][32][33] Therefore, we hypothesize that KMT2C and PEG3 mutations result in a higher TMB level in PAAD, activating the immune system to attack cancer. 34 During the progression of metastatic epithelial cancer, antigen mutations have recently been found in peripheral blood samples from patients with KMT2C mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to causing mutation-derived neoantigens, a high TMB can make tumors more immunogenic by inducing a T-cell-mediated immune response and releasing new antigens. 3033 Therefore, we hypothesize that KMT2C and PEG3 mutations result in a higher TMB level in PAAD, activating the immune system to attack cancer. 34…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al found that RYR2 3′UTR polymorphisms remained significant in the genetic susceptibility of progesterone receptor positive breast cancer [25]. Liu et al found the RYR2 mutation was linked to a greater TMB and a better clinical outcome by enhancing the antitumor immune response in breast cancer and esophageal adenocarcinoma [26]. In nonsmall cell lung cancer, RYR2 mutation may prolong survival via downregulation of DKK1 and upregulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Schmitt, K et al found differential promoter methylation status and expression level of RYR2 in head and neck tumor, suggesting that reduced expression of RYR2 in adjacent tissues and precancerous lesions may potentially indicate poor survival and impending malignancy [6]. In oesophageal cancer, the RYR2 mutation upregulated signalling pathways involved in the immune response and enhanced anti-tumor immunity [12]. The RYR2 rs12594 mutation (occurring in the 3 0 -UTR) also significantly reduced the risk of developing breast cancer [13].…”
Section: Introductionmentioning
confidence: 99%